Buddhist funeral cultures of Southeast Asia and China - Williams, Paul, 1950-; Ladwig, Patrice (Cambridge : Cambridge University Press, 2012)
"The centrality of death rituals has in anthropologically informed studies of Buddhism been little documented. The current volume brings together a range of perspectives on Buddhist death rituals including ethnographic, textual, historical and theoretically informed accounts, and presents the diversity of the Buddhist funeral cultures of mainland Southeast Asia and China. It arises out of the University of Bristol's Centre for Buddhist Studies research project Buddhist Death Rituals in Southeast Asia and China, funded by the United Kingdom's Arts and Humanities Research Council. This project involved extensive new research in Thailand, Laos and China. Other items from that project included several public exhibitions, extensive stills photographs, and several video films. The project-team produced two 30 minutes films on the ghost festival in Laos and China, one on urban funerals in Chiang Mai (Thailand) and several shorter clips dealing with funeral cultures in Laos, Thailand and China. Most of this material (and an extensive bibliography on the topic) is available free of charge from the project website located at the webpage of the Department of Theology and Religious Studies (Centre for Buddhist Studies) at the University of Bristol"--
1. Introduction: Buddhist funeral cultures / Patrice Ladwig and Paul Williams -- 2. Chanting as 'bricolage technique': a comparison of South and Southeast Asian funeral recitation / Rita Langer -- 3. Weaving life out of death: the craft of the rag robe in Cambodian ritual technology / Erik W. Davis -- 4. Corpses and cloth: illustrations of the paṃsukũla ceremony in Thai manuscripts / M.L. Pattaratorn Chirapravati -- 5. Good death, bad death and ritual restructurings: the New Year ceremonies of the Phunoy in northern Laos / Vanina Bouté -- 6. Feeding the dead: ghosts, materiality and merit in a Lao Buddhist festival for the deceased / Patrice Ladwig -- 7. Funeral rituals, bad death and the protection of social space among the Arakanese (Burma) / Alexandra de Mersan -- 8. Theatre of death and rebirth: monks' funerals in Burma / François Robinne -- 9. From bones to ashes: the Teochiu management of bad death in China and overseas / Bernard Formoso -- 10. For Buddhas, families and ghosts: the transformation of the Ghost Festival into a Dharma assembly in southeast China / Ingmar Heise -- 11. Xianghua foshi (incense and flower Buddhist rites): a local Buddhist funeral ritual tradition in southeastern China / Yik Fai Tam -- 12. Buddhist passports to the other world: a study of modern and early medieval Chinese Buddhist mortuary documents / Frederick Shih-Chung Chen.
Print version record.
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: Buddhist funeral rites and ceremonies -- Southeast Asia; Buddhist funeral rites and ceremonies -- China; Funérailles -- Rites et cérémonies bouddhiques -- Asie du Sud-Est.; Funérailles -- Rites et cérémonies bouddhiques -- Chine; RELIGION -- Buddhism -- General (see also PHILOSOPHY -- Buddhist); Buddhist funeral rites and ceremonies; China; Southeast Asia